2020
DOI: 10.1016/j.tifs.2019.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into chemical and pharmacological studies of bee bread

Abstract: Background: Bee bread is a product of the fermentation of a mixture of pollen, nectar and bee saliva that is inoculated by a wide range of bacteria and yeasts necessary for fermentation after storage in comb cells. Bee bread is regarded as the chief protein resource that bees can utilize, especially for feeding of larvae and adults. Since ancient times, bee bread has been used in different cultures for several nutritional and therapeutic purposes. Scope and approach: In this review, we attempt to highlight the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 96 publications
2
72
0
Order By: Relevance
“…Bee bread or ambrosia is a unique product for humans and bees, and is formed from pollen, honey and secretions of bees’ salivary glands [ 1 , 2 ] which are packed by the bees into the honeycomb and covered with wax and honey. During the preservation, the content is submitted to lactic fermentation caused by bacteria and yeast in the bee nest medium [ 3 ], thus resulting in bee bread which has a caramel color [ 4 ], a tangy taste which is given by its citrus, flowers or other fruit flavors [ 5 ]. Bee bread is the main food for the beehive, and particularly for larvae and young worker bees that produce royal jelly [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bee bread or ambrosia is a unique product for humans and bees, and is formed from pollen, honey and secretions of bees’ salivary glands [ 1 , 2 ] which are packed by the bees into the honeycomb and covered with wax and honey. During the preservation, the content is submitted to lactic fermentation caused by bacteria and yeast in the bee nest medium [ 3 ], thus resulting in bee bread which has a caramel color [ 4 ], a tangy taste which is given by its citrus, flowers or other fruit flavors [ 5 ]. Bee bread is the main food for the beehive, and particularly for larvae and young worker bees that produce royal jelly [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, bee bread has been used in different cultures for several nutritional and therapeutic purposes. Different biological effects and dietary properties have been attributed to bee bread, including antimicrobial, antioxidant, anticancer, and antiinflammatory activities (Khalifa et al, 2019). The chemical content of bee bread has been revealed in various studies (Nagai et al, 2005;Kaplan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bee bread is composed of well-balanced proteins containing all essential amino acids, the full spectrum of vitamins (C, B1, B2, E, H, P, nicotinic acid, folic acid), pantothenic acid, pigments, and other biologically active compounds, like enzymes such as saccharase, amylase, phosphatases, flavonoids, carotenoids, and hormones. Bee bread also contains over 25 different micro-and macroelements such as iron, calcium, phosphorus, potassium, copper, zinc, selenium, and magnesium (Nagai et al, 2005;Khalifa et al, 2019). It was reported that bee bread involves more reduced sugar than the pollen of the same plant, as well as vitamin K and microorganisms' digestive enzymes (Haydak, 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite beebread’s excellent health properties, the scientific community is little interested in its study. Beebread composition varies according to the origin of the pollen but is mainly composed of water, proteins, carbohydrates, lipids, inorganic elements, and various other minor components such as decanoic acid, gamma globulin, nucleic acids, vitamins B and C, pantothenic acid, biopterin, neopterin, acetylcholine, and reproductive hormones, among others [ 5 , 6 ]. Considerable amount of information can be found in the literature on the types of polyphenol compounds contained in bee bread [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%